Metabolic effects of cross-sex hormone therapy in transgender individuals in Taiwan. Issue 3 (3rd March 2021) - Liu, Yu-Hsien; Wu, Tsung-Hui; Chu, Chia-Huei; Lin, Yi-Chun; Lin, Liang-Yu
Abstract : Background: Transgender individuals often require gender-affirming interventions, such as endogenous sex hormone inhibition or gender-affirming hormone therapy (HT), while there is discordance between their body and gender identity. However, a recent study found that the incidence of cardiovascular events is higher in transgender patients receiving cross-sex HT. The aim of this study was to investigate the metabolic effects of an altered sex hormone profile. Methods: This retrospective study, conducted in a referral center in Northern Taiwan, analyzed metabolic changes over time in 65 trans masculine and 45 trans feminine persons. The transgender individuals were examined at 4 time points: before the gender affirming HT, as well as 3, 6, and 12 months following treatment. Results: Compared with baseline measurements, the trans masculine patients showed significant increases in body mass index (BMI) (22.6 ± 0.3 vs 23.3 ± 0.4 kg/m 2 ; p < 0.001; t = 3M), low-density lipoprotein cholesterol (124.3 ± 3.7 vs 131.3 ± 3.9 mg/dL; p = 0.03; t = 12M), creatinine (0.75 ± 0.01 vs 0.83 ± 0.14 mg/dL; p < 0.001; t = 12M), and hemoglobin (13.5 ± 0.7 vs 15.2 ± 0.2 g/dL; p < 0.001; t = 12M), as well as decreased high-density lipoprotein cholesterol (57 ± 2.1 vs 51 ± 2.0 mg/dL; p < 0.001; t = 12M). The trans feminine patients had reduced low-density lipoprotein cholesterol (104.2 ± 3.2 vs 100.8 ± 3.5 mg/dL; p = 0.05; t = 3M), hemoglobin (14.0 ± 0.1 vs 13.5 ± 0.1 g/dL; p = 0.008; t = 12M), and creatinine (0.82 ± 0.01 vs 0.79 ± 0.14 mg/dL; p < 0.001; t = 3M) compared with baseline data. In addition, most of these metabolic effects persisted during the follow-up period. Conclusion: This observational, retrospective study revealed that gender-affirming HT increased the relative cardiovascular risk in trans masculine individuals.